Saluran Pemasaran Telur Ayam Ras Di Desa Sunju, Kecamatan Marawola, Kabupaten Sigi - Mahbit Kusnandy; Rita Yunus; Wiri Wirastuti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Community service is the implementation of science experience directly in the community. In general, animal husbandry in Sunju Village is directed at realizing advanced, efficient and resilient animal husbandry conditions. Efforts to increase livestock business opportunities, especially the broiler poultry business, require comprehensive regional policy support that can encourage increased productivity, product quality and market competitiveness. This service aims to increase the speed of the process of increasing the ability of human resources in accordance with the growth rate of development and can provide an understanding to laying hens about marketing channels from the farmer level to the final consumer and can also independently analyze the condition of the marketing channel in each channel in Sunju Village, Marawola District, Sigi Regency. The method used in this service is a survey to the intended location, interviews and socialization to farmers. The results of the service changed the information data in Sunju Village focusing on product marketing in the marketing channel. The importance of the results of this service is that we are more about the various kinds of marketing channels that exist.